Combined familial adenosine deaminase and purine nucleoside phosphorylase deficiencies. Issue 8 (August 1988) - Shanon, A; Levin, S; Holtzman, F; Brock-Sinai, F; Abu-Said, A
Abstract : We studied an Arab family in which two infants died of severe combined immunodeficiency caused by adenosine deaminase (ADA) deficiency. One infant had purine nucleoside phosphorylase (PNP) activity in the leucocytes only half that of normal. Four other infant siblings had previously died from infections before the age of 2 months. Hyperpigmented skin lesions preceded death in three cases. The healthy parents and three healthy siblings aged 4-9 years had varying degrees of both ADA and PNP deficiencies in both white and red cells. ADA deficiency was pronounced in two siblings, and mild in the third and in the parents, and PNP activity was severely deficient in one sibling, and moderately deficient in the parents and other two siblings, who were all well. Complete absence of ADA from white cells lead to the development of severe combined immunodeficiency, but even minimal residual ADA and PNP activity allowed maturation of the immune system with normal immune function.